Adenovirus Lacking E1b Efficiently Induces Cytopathic Effect in HPV-16-Positive Murine Cancer Cells via Virus Replication and Apoptosis. (2nd January 2018) - Martinez-Jaramillo, Elvis; Garza-Morales, Rodolfo; Wechman, Stephen L.; Montes de Oca-Luna, Roberto; Saucedo-Cardenas, Odila; Shirwan, Haval; Yolcu, Esma; McMasters, Kelly M.; Gomez-Gutierrez, Jorge G.
ABSTRACT: Conditionally replicative adenoviruses (CRAds) replicate poorly in murine cancer cells; however, E1b -deleted CRAds may replicate effectively in HPV16- E6/E7 -positive murine cancer cells (TC-1). The HPV16 E7 open reading frame encodes functions analogous to these deleted adenovirus E1 proteins. In this study, an E1b -deleted CRAd (Adhz60) was evaluated for its ability to replicate and induce oncolysis in TC-1 cells. Adhz60-mediated oncolysis was similar in TC-1 and HeLa cells. Productive viral replication was evident based on expression of E1A and hexon, production of infectious virus progeny, and Adhz60-induced apoptosis. The results suggest that TC-1 murine cancer cells allow Adhz60 replication and oncolysis.